2003
DOI: 10.1007/s00018-002-3014-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroreplacement therapy and stem cell biology under disease conditions

Abstract: Recent advances in stem cell technology are expanding our ability to replace a variety of cells throughout the body. In the past, neurological diseases caused by the degeneration of neuronal cells were considered incurable because of a long-held 'truism'; neurons do not regenerate during adulthood. However, this statement has been challenged, and we have now found much evidence that the brain is indeed capable of regenerating neurons after maturing. Based on this new concept, researchers have shown neural diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 113 publications
0
16
0
Order By: Relevance
“…Galli et al. 2005;Harris, 2003;Martino, 2004;Sohn and Gussoni, 2004;Sugaya, 2003a;Sugaya, 2003b) and (6) development (which distinguishes between genetic and other signaling events that lead to the fiber architecture of a particular muscle, body segment or the vascular supply in a muscle anlage) (e.g. BrandSaberi, 2005;Brand-Saberi and Christ, 1999;Denetclaw, Jr et al, 2001;Denetclaw and Ordahl, 2000;Duxson et al, 1986;Ordahl, 1999;Williams and Ordahl, 2000).…”
Section: Skeletal Muscle Plasticitymentioning
confidence: 99%
“…Galli et al. 2005;Harris, 2003;Martino, 2004;Sohn and Gussoni, 2004;Sugaya, 2003a;Sugaya, 2003b) and (6) development (which distinguishes between genetic and other signaling events that lead to the fiber architecture of a particular muscle, body segment or the vascular supply in a muscle anlage) (e.g. BrandSaberi, 2005;Brand-Saberi and Christ, 1999;Denetclaw, Jr et al, 2001;Denetclaw and Ordahl, 2000;Duxson et al, 1986;Ordahl, 1999;Williams and Ordahl, 2000).…”
Section: Skeletal Muscle Plasticitymentioning
confidence: 99%
“…In animal models of ALS, several studies showed that transplantation of cells derived from the human teratocarcinoma cell line or human umbilical cord blood resulted in beneficial effects. However, neuroprotection was suggested to be the main cause of the observed benefits rather than the direct motor neuron replacement (Ende et al 2000;Garbuzova-Davis et al 2002, 2003.…”
Section: The Concept Of Cell Replacementmentioning
confidence: 93%
“…In AD, long projections and the expression of nerve growth factor receptors led some researchers to declare basal forebrain cholinergic neurons irreplaceable (Sugaya 2003). Although there are no reports at the moment of clinical use of embryonic transplants in AD patients, several works have demonstrated that cholinergic-rich cells of fetal origin can improve the performance in animal models of cholinergic depletion (Gage and Bjorklund 1986;Hodges et al 1991a, b;Muir et al 1992;Grigoryan et al 2000).…”
Section: The Concept Of Cell Replacementmentioning
confidence: 96%
“…The latter may not apply to diseases which directly affect all resident cells in the CNS (e.g., HD) but may be of critical importance for traumatic or vascular brain lesions. Finally, some of the trophic factors which may improve the survival of grafted cells could represent, per se, a therapeutic alternative (e.g., GDNF, reelin 44 ). In a sense, their use means "to teach the brain to graft himself with its own cells.…”
Section: Discussionmentioning
confidence: 99%